Design and implementation of real‐time monitoring and control system supported with IOS/Android application for industrial furnaces. Issue 9 (11th May 2018) - Yılmaz, Cemal; Yılmaz, Ercan Nurcan; Işık, Mehmet Fatih; Usalan, Mehmet Ali Sinan; Sönmez, Yusuf; Özdemir, Veysel
Abstract : SCADA (supervisory control and data acquisition) systems have been used widely in the manufacturing process in parallel to the rapid advancement of technology in recent years. The quality of products in these systems depends on direct process monitoring and control. Therefore, in this study, a SCADA‐based scale model is developed for real‐time monitoring and control of an industrial furnace by using Android/IOS‐based smartphones. To achieve the desired temperature in the furnace and to keep the energy saving constant, a PLC‐based SCADA system was designed. In the designed system, the furnace temperature is measured continuously by sensors and the furnace voltage is set as analog in order to reach the desired temperature as soon as possible. Different PID parameters are used to achieve this aim. Thus, the product quality is increased and energy efficiency is achieved. © 2018 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.